2001
DOI: 10.1101/gad.921601
|View full text |Cite
|
Sign up to set email alerts
|

The Swi5 activator recruits the Mediator complex to theHOpromoter without RNA polymerase II

Abstract: Regulation of HO gene expression in the yeast

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
156
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(170 citation statements)
references
References 69 publications
13
156
1
Order By: Relevance
“…This simple model could perhaps also explain the mild phenotypes that are identified for ⌬spsrb8 and ⌬sptrap240. The recruitment of Mediator to the yeast HO promoter and to Drosophila HSF-binding sites without pol II supports this view (34)(35)(36). Thus, lack of Srb8-11 may have more profound effects on the kinetics͞timing of transcriptional activation at specific promoters, rather than on the overall levels of gene expression.…”
Section: Discussionsupporting
confidence: 51%
“…This simple model could perhaps also explain the mild phenotypes that are identified for ⌬spsrb8 and ⌬sptrap240. The recruitment of Mediator to the yeast HO promoter and to Drosophila HSF-binding sites without pol II supports this view (34)(35)(36). Thus, lack of Srb8-11 may have more profound effects on the kinetics͞timing of transcriptional activation at specific promoters, rather than on the overall levels of gene expression.…”
Section: Discussionsupporting
confidence: 51%
“…This breadth could ref lect a range of preferred binding sites at different promoters or, alternatively, could indicate that Mediator is distinctly present at both UAS and proximal promoter regions (perhaps at different times) of active genes. There is precedence for this idea in studies of the HO promoter in yeast and heat shock promoters in Drosophila (44,46). Interestingly, Rgr1 association with the core promoter regions of the genes examined here was substantially decreased in srb4 ts yeast, but association of Rgr1 with the UAS region showed a less marked decrease (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…7B), and thus, both chromatin remodeling and histone acetylation are required for these two complexes to associate stably at HO. Swi5 also interacts directly with Mediator, and both Swi5 and SWI/SNF are required for Mediator binding to the HO promoter (12). We speculate that there may also be interactions between SAGA and Mediator that stabilize the binding of both complexes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Swi5 interacts directly with SWI/SNF (66), and Swi5 is required for the subsequent recruitment of SWI/SNF. The Mediator complex then binds to the URS1 region, long before the arrival of RNA polymerase II (Pol II) (12). There is a direct interaction between Mediator and Swi5, and genetic experiments have shown that both Swi5 and SWI/SNF are required for Mediator recruitment (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation